2010
DOI: 10.1007/s00330-010-1899-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver iron concentration quantification by MRI: are recommended protocols accurate enough for clinical practice?

Abstract: The assessment of LIC with the URennes method was useful in 74.3% of the patients to rule out or to diagnose high iron overload. The method has a tendency to overestimate overload, which limits its diagnostic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Comparing our data with this study, however, we also found a significant difference between the calibration curve given by Virtanen et al and our data. In accordance with other studies, our data indicate that the SIR method apparently overestimates LIC [23]. This may be crucial when therapeutic decisions are based on the results from noninvasive hepatic iron quantification.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Comparing our data with this study, however, we also found a significant difference between the calibration curve given by Virtanen et al and our data. In accordance with other studies, our data indicate that the SIR method apparently overestimates LIC [23]. This may be crucial when therapeutic decisions are based on the results from noninvasive hepatic iron quantification.…”
supporting
confidence: 91%
“…The correlation between both methods was still significant (r = 0.85). Castiella et al recently demonstrated that the SIR method has a tendency to overestimate LIC and that it could measure iron up to 350 μmol/g (19.5 mg/g) [23]. None of our patients had an LIC at that level, although one patient with HFE-associated hemochromatosis had an LIC of 11.64 mg/g which is quite high for that disease.…”
mentioning
confidence: 52%
“…Of those, magnetic resonance imaging (MRI) using gradient-echo sequences with long echo times as well as recently introduced multi-echo gradient-echo sequences have proven to be promising methods [3,4]. However, MRI showed limitations including an overestimation of the LIC [5], and an inability to quantify LIC above 300 μmol/g owing to the strong paramagnetic effect of iron resulting in signal loss [6].…”
Section: Introductionmentioning
confidence: 99%
“…A liver biopsy requires a patient to stay in the hospital and is expensive. The MRI tends to overestimate the iron concentration because of its magnetic field [1]. For accurate measurement of the iron concentration, X-ray computed tomography (CT) is a very promising method.…”
Section: Introductionmentioning
confidence: 99%